Cover Image, Volume 38, Issue 12. Issue 12 (1st November 2017) - Zhang, Yue; Zhou, Tiantian; Niu, Yayan; He, Meiling; Wang, Can; Liu, Meng; Yang, Junhua; Zhang, Yonghong; Zhou, Jianping; Fukuda, Koichi; Qin, Jun; Dong, Ningzheng; et al.
Abstract : On the cover : This cover image, by Yue Zhang et al., is based on the Research Article Identification and functional analysis of CORIN variants in hypertensive patients, Pages 1700–1710. DOI:10.1002/humu.23318 .